Teaching Writing Descriptive Text by Using Picture Word Inductive Model (PWIM) to the Eighth Grade Students of SMP Negeri 2 Lawang Wetan in Musi Banyuasin Districs - Ferri Hidayad (Universitas PGRI Palembang, 2017)
The objective of this study was to find out whether or not there was a significant difference in descriptive writing achievement of the eighth grade students of SMP Negeri 2 Lawang Wetan in Musi Banyuasin Districts before and after they were taught by using Picture Word Inductive Model (PWIM). The population of this study was all of the eighth grade students of SMP Negeri 2 Lawang Wetan in academic year of 2017/2018 with the total number of 192 students. Sixty four students were taken as a sample and divided equally into two groups, experimental and control group. The method used in this study was quasi-experimental design which used pretest-posttest design. Writing test was used as the instrument in collecting the data. The test was administered twice as the pre-test and the post-test. The result of the test was analyzed by using T-test (paired sample and independent sample t-test) through Statistical Package for Social Science (SPSS) 21 for Windows. The results of paired sample t-test showed that there was a significant difference in descriptive writing achievement of the eighth grade students of SMP Negeri 2 Lawang Wetan before and after they were taught by PWIM. Based on the results of independent sample t-test, it was found that there was a significant difference in descriptive writing achievement between the students who were taught by using PWIM and those who were not.Keywords: teaching writing descriptive text, picture word inductive model (PWIM)